Circles, when graphed on the coordinate plane, have an equation of x2 + y2 = r2 where r is the radius (standard form) when the center of the circle is the origin. When the center of the circle is (h, k) and the radius is of length r, the equation of a circle (standard form) is (x - h)2 + (y - k)2 = r2.
Example: 1. Problem: Find the center and radius of (x - 2)sq + (y + 3)sq = 16. Then graph the circle.
Solution: Rewrite the equation in standard form. (x - 2)sq + [y - (-3)]sq = 4sq
The center is (2, -3) and the radius is 4. The graph is easy to draw, especially if you use a compass. The figure below is the graph of the solution.
here are my questions:
~How did they get -2 and -3 as the center point of the circle?
~How come the formula change from x2+y2= r2 to (x-h)2 + (y-k)2 = R2?
~Sorry i'm kind of dumb on these things. =) thank you